2000
DOI: 10.1117/12.410904
|View full text |Cite
|
Sign up to set email alerts
|

<title>Transcoding characteristics of Web images</title>

Abstract: Transcoding is a technique employed by network proxies to dynamically customize multimedia objects for prevailing network conditions and individual client characteristics. Transcoding can be performed along a number of different axes and the specific transcoding technique used depends on the type of multimedia object. Our goal in this paper is to understand the nature of typical Internet images and their transcoding characteristics. We focus our attention on transcodings intended to customize an image for file… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
0

Year Published

2003
2003
2007
2007

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 20 publications
2
19
0
Order By: Relevance
“…Workload 1 is based on proxy traces belonging to the nodes of the IRCache infrastructure. We can assume that Workload 1 captures a realistic scenario, because we found that the statistical characteristics of the images contained in the workload (e.g., file size, JPEG quality factor, number of colors of GIF images) are very close to the results reported in [4]. Workload 2 is characterized by image files much larger than those contained in Workload 1, thus requiring in average a transcoding cost about three times higher.…”
Section: Resultsmentioning
confidence: 70%
See 1 more Smart Citation
“…Workload 1 is based on proxy traces belonging to the nodes of the IRCache infrastructure. We can assume that Workload 1 captures a realistic scenario, because we found that the statistical characteristics of the images contained in the workload (e.g., file size, JPEG quality factor, number of colors of GIF images) are very close to the results reported in [4]. Workload 2 is characterized by image files much larger than those contained in Workload 1, thus requiring in average a transcoding cost about three times higher.…”
Section: Resultsmentioning
confidence: 70%
“…The classes of devices range from high-end workstations/PCs which can consume every object in its original form, to midrange PCs or laptops, set-top boxes, hand-held PCs, personal digital assistants, and cellular phones. We consider that transcoding is applied only to image objects (both GIF and JPEG formats), as more than 70% of the files requested in the Web still belongs to this class (e.g., [4]). In the system model, we assume that traditional devices, such as PCs and laptops, are still more popular than other client devices; hence, 25% of client requests come from PCs not requiring any transcoding, 25% from laptops with low or null necessity of content adaptation, while the remaining 50% of requests is equally divided among the other four classes of devices with major transcoding requirements.…”
Section: Resultsmentioning
confidence: 99%
“…We downloaded the resources from their content servers and placed them on our content server. We performed some characterization on the images in the light workload, such as file size, JPEG quality factor, and number of colors of GIF images, and found that they are very close to the results reported in [6]. Hence, we can assume that our workload captures a realistic scenario of present Web requests.…”
Section: Client and Workload Modelsmentioning
confidence: 78%
“…In this paper, we consider that transcoding operations are applied only to image resources (both GIF and JPEG formats), as more than 70% of the files requested on the Web still belongs to this class [6]. However, in our experiments we also consider a likely future scenario where the transcoding operations have higher costs because of the larger percentage of non-textual resources.…”
Section: Client and Workload Modelsmentioning
confidence: 99%
See 1 more Smart Citation